Case report: Rubella virus-associated cutaneous granuloma in an adult with TAP1 deficiency - Wang, Qiaohui; Su, Huilin; Han, Jiande; Yang, Juhua; Lin, Naiyu (Frontiers in Immunology, 2024)
Rubella virus-associated granulomas commonly occur in immunocompromised individuals, exhibiting a diverse range of clinical presentations. These manifestations can vary from predominantly superficial cutaneous plaques or nonulcerative nodules to more severe deep ulcerative lesions, often accompanied by extensive necrosis and significant tissue destruction. TAP1 deficiency, an exceedingly rare primary immune-deficiency disorder, presents with severe chronic sino-pulmonary infection and cutaneous granulomas. This report highlights the occurrence of rubella virus-associated cutaneous granulomas in patients with TAP1 deficiency. Notably, the pathogenic mutation responsible for TAP1 deficiency stems from a novel genetic alteration that has not been previously reported. This novel observation holds potential significance for the field of diagnosis and investigative efforts in the context of immunodeficiency disorders.